Analisis kemampuan koneksi matematis siswa pada pembelajaran luring pasca pandemi - Fentiawati Trysna Dinata; Husnul Khatimah Rusyid; Siti Fatimah; Tatang Herman (IKIP Siliwangi, 2023)
The study aims to analyze the ability of mathematical connections in a sequence and series of materials conducted when learning offline after previously applied online learning. This type of research is qualitative with data collection techniques, namely mathematical connection ability tests and interviews. The subjects of the study consisted of 4 class XI SMK students in Bandung Regency who had previously studied sequence and series online. Analysis carried out on mathematical connection ability seen from indicators of connection ability is understanding the equivalent representation of the same concept or procedure, looking for connections with procedures to other procedures in equivalent representations, using mathematics in everyday life and using connections between mathematical topics, and between mathematical topics and other topics. The results of the analysis conducted show that the achievement of mathematical connection ability for each indicator is still not achieved, so students' mathematical connection ability is still relatively low.Â